2011
DOI: 10.1167/iovs.11-7498
|View full text |Cite
|
Sign up to set email alerts
|

Egr1 Expression Is Induced Following Glatiramer Acetate Immunotherapy in Rodent Models of Glaucoma and Alzheimer's Disease

Abstract: This study presents global gene expression profiles associated with GA immunization in a glaucoma rat model. Moreover, it identifies EGR1 transcription factor as a potential mediator for GA-induced neuroprotection in both glaucoma and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 112 publications
(84 reference statements)
3
55
0
Order By: Relevance
“…Previous studies have shown that the Egr-1 level is up-regulated in AD brains (18 -21, 37). Furthermore, levels of both BACE-1 and Egr-1 are elevated in the brain during aging (22,38,39), hypoxia, brain injury, ischemia, and inflammation (13,14) and in AD mouse models (13,21,23). These observations together indicate that Egr-1 is an activator of BACE-1 in the CNS and suggest that Egr-1 plays role in the up-regulation of levels of BACE-1 and A␤ in AD brain.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that the Egr-1 level is up-regulated in AD brains (18 -21, 37). Furthermore, levels of both BACE-1 and Egr-1 are elevated in the brain during aging (22,38,39), hypoxia, brain injury, ischemia, and inflammation (13,14) and in AD mouse models (13,21,23). These observations together indicate that Egr-1 is an activator of BACE-1 in the CNS and suggest that Egr-1 plays role in the up-regulation of levels of BACE-1 and A␤ in AD brain.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, at this time point, the aminoacyl t-RNA biosynthesis pathway was downregulated, which indicates an alteration of translation and suggest that protein synthesis in the injured retinas is below normal levels, as it has been reported in glaucoma and ischemia. 57,58 One of the most consistent differences observed at 14 days post-IONC was associated with carbohydrate metabolism. Glucose (Glc) and glucose-6-phospate (Glc-6-P) levels were nearly 3-fold higher 14 days post-IONC, whereas additional glycolytic intermediates (3-phosphoglycerate, 2-phospoglycer- ate, and lactate) were slightly higher, but not significantly different from the control ( Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages readily absorb amyloid fibrils in vitro (59,60) and seem more efficient than microglia at restricting Aβ plaques in models of AD (30, 31, 36, 38). ADtg mice immunized with glatiramer acetate or DCs loaded with the peptide MOG45D had an increased cerebral infiltration of monocytes that resulted in substantial attenuation of AD pathology (31,36,61). These mice also had reduced cognitive impairment (62).…”
Section: Discussionmentioning
confidence: 99%
“…For brain-soluble and -insoluble ELISA analysis, brain tissues were homogenized in PBS buffer with 0.5% Triton X-100 and a 1X protease inhibitor cocktail set I (Calbiochem). After removal of cell debris, the homogenate was centrifuged at 10,000 g for 20 minutes at 4°C (36,61). The supernatant was considered the soluble fraction and was used to assess soluble Aβ.…”
Section: Methodsmentioning
confidence: 99%